Evaluation of imputation accuracy using the combination of two high-density panels in Nelore beef cattle - Bernardes, Priscila Arrigucci [UNESP]; Nascimento, Guilherme Batista do; Savegnago, Rodrigo Pelicioni; Buzanskas, Marcos Eli; Watanabe, Rafael Nakamura [UNESP]; Almeida Regitano, Luciana Correia de; Coutinho, Luiz Lehmann; Gondro, Cedric; Munari, Danisio Prado [UNESP] (Nature Publishing Group, 2019)
This study compared imputation from lower-density commercial and customized panels to high-density panels and a combined panel (Illumina and Affymetrix) in Nelore beef cattle. Additionally, linkage disequilibrium and haplotype block conformation were estimated in individual high-density panels and compared with corresponding values in the combined panel after imputation. Overall, 814 animals were genotyped using BovineHD BeadChip (IllumHD), and 93 of these animals were also genotyped using the Axion Genome-Wide BOS 1 Array Plate (AffyHD). In general, customization considering linkage disequilibrium and minor allele frequency had the highest accuracies. The IllumHD panel had higher values of linkage disequilibrium for short distances between SNPs than AffyHD and the combined panel. The combined panel had an increased number of small haplotype blocks. The use of a combined panel is recommended due to its increased density and number of haplotype blocks, which in turn increase the probability of a marker being close to a quantitative trait locus of interest. Considering common SNPs between IllumHD and AffyHD for the customization of a low-density panel increases the imputation accuracy for IllumHD, AffyHD and the combined panel.